Monitoring the Redox Status in Multiple Sclerosis - Tanaka, Masaru (Biomedicines, 2020)
Worldwide, over 2.2 million people suffer from multiple sclerosis (MS), a multifactorial demyelinating disease of the central nervous system. MS is characterized by a wide range of motor, autonomic, and psychobehavioral symptoms, including depression, anxiety, and dementia. The blood, cerebrospinal fluid, and postmortem brain samples of MS patients provide evidence on the disturbance of reduction-oxidation (redox) homeostasis, such as the alterations of oxidative and antioxidative enzyme activities and the presence of degradation products. This review article discusses the components of redox homeostasis, including reactive chemical species, oxidative enzymes, antioxidative enzymes, and degradation products. The reactive chemical species cover frequently discussed reactive oxygen/nitrogen species, infrequently featured reactive chemicals such as sulfur, carbonyl, halogen, selenium, and nucleophilic species that potentially act as reductive, as well as pro-oxidative stressors. The antioxidative enzyme systems cover the nuclear factor erythroid-2-related factor 2 (NRF2)-Kelch-like ECH-associated protein 1 (KEAP1) signaling pathway. The NRF2 and other transcriptional factors potentially become a biomarker sensitive to the initial phase of oxidative stress. Altered components of the redox homeostasis in MS were discussed in search of a diagnostic, prognostic, predictive, and/or therapeutic biomarker. Finally, monitoring the battery of reactive chemical species, oxidative enzymes, antioxidative enzymes, and degradation products helps to evaluate the redox status of MS patients to expedite the building of personalized treatment plans for the sake of a better quality of life.